The principle of freedom of investment and trade is a legal basis freedom of competition - Zaoueche, Chouaib (Journal of Human Sciences, 2021)
After the transformation of the market economy, the Algerian legislator stated its goal to improve the business climate and encourage the prosperity of enterprises, especially with the emergence of strong indicators of a new economic crisis, To embody this, he initiated qualitative reforms that touched the fundamental principle expressed in the principle of freedom of investment and trade, to expand the scope of access to private investment in various economic activities.However, this expansion was accompanied by a dedication to a general restriction that limits the scope of people to engage in certain activities, which negatively affects national economic development, especially as private investors prefer to invest in markets where they enjoy freedom of competition.